Income Equality in the Nordic Countries: Myths, Facts, and Lessons - Magne Mogstad; Kjell G. Salvanes; Gaute Torsvik (Institute of Labor Economics (IZA), 2025)
Policymakers, public commentators, and researchers often cite the Nordic countries as examples of a social and economic model that successfully combines low income inequality with prosperity and growth. This article aims to critically assess this claim by integrating theoretical perspectives and empirical evidence to illustrate how the Nordic model functions and why these countries experience low inequality. Our analysis suggests that income equality in the Nordics is primarily driven by a significant compression of hourly wages, reducing the returns to labor market skills and education. This appears to be achieved through a wage bargaining system characterized by strong coordination both within and across industries. This finding contrasts with other commonly cited explanations for Nordic income equality, such as redistribution through the taxtransfer system, public spending on goods that complement employment, and public policies aimed at equalizing skills and human capital distribution. We consider the potential lessons for other economies that seek to reduce income equality. We conclude by discussing several underexplored or unresolved questions and issues.
Keywords: 330; facts and myths; Nordic Model